Comparative Efficacy of Oxitard Capsules and Immusante Tablets in Early Stages of Oral Submucous Fibrosis - A Randomized Controlled Trial - Dash, Kabir Suman; Mathur, Anmol; Rajpurohit, Ladusingh; Kale, Sonal (Journal of Health Science and Medical Research, 2024)
Objective: Oral submucous fibrosis (OSMF) is manifested by symptoms such as palpable fibrotic bands, ulceration, presence of stiffness in the mouth and lip, xerostomia, pigmentation in the oral mucosal layer, and burning sensation and drying of the mouth. It poses a challenge for researchers as there is no viable therapy for this gradually debilitating disorder with a high malignancy potential. Ayurveda is a traditional medicinal practice of the past and present times which can be useful in providing a viable cure. Thus, the current study was designed to assess and compare the effect of Oxitard capsule and Immusante tablet on the clinical and subjective symptoms of OSMF. Material and Methods: The study included 36 patients with clinically diagnosed OSMF who were split evenly into two groups: Group A, the Oxitard group, and Group B, the Immusante group. For three months, Group A received two Oxitard capsules twice daily, while Group B received two Immusante tablets twice daily. At regular intervals, the clinical parameters were evaluated, and the data were analysed using repeated measures ANOVA and the Bonferroni post hoc test. P-value≤0.05 was regarded as statistically significant. Results: On assessment of mouth opening, tongue protrusion, cheek flexibility and subjective symptoms there was significant improvement reported in both groups. In group comparison, the Oxitard and Immusante groups showed a significant difference in cheek flexibility at 3 months. There were no significant differences in subjective symptoms in either of the groups pre- and post-treatment. Conclusion: Efficacy of both the drugs were equall was found to be similar when used as an adjunct to tobacco cessation counselling in the management of early stages of oral submucous fibrosis when used as an adjunct to behavioral management.